Mucosal healing and quality of life in therapeutic goals of ulcerative colitis: occurrence and related factors of functional bowel disorder-like symptoms. (April 2022) - Lin, Lihui; Wang, Tianqi; Lu, Yaming; Chen, Peng; Zhang, Yingfan; Zu, Xiaoman; Chen, Baili; Mao, Ren; Feng, Rui; Cui, Yi; Zhang, Shenghong; He, Yao
Background: Mucosal healing (MH) is considered the preferred therapeutic target for ulcerative colitis (UC). Impaired quality of life (QoL), irritable bowel syndrome (IBS)-like symptoms, and functional bowel symptoms have been reported in several inactive patients with UC. This study aims to assess the occurrence of functional bowel disorders (FBD)-like symptoms and QoL in UC patients with MH, and to explore the factors related to FBD-like symptoms. Methods: UC patients with MH (Mayo endoscopic score, MES = 0 or 1) were required to complete the Rome IV diagnostic questionnaire, the 32-item version of Inflammatory Bowel Disease Questionnaire (IBDQ-32), the 36-item short form healthy survey questionnaire (SF-36), and the Hospital Anxiety and Depression Scale (HADS). UC patients who did not achieve MH (MES > 1) completed the IBDQ-32, the SF-36, and the HADS. Community-dwelling healthy controls (HCs) completed the SF-36 and the HADS. Results: Among the 119 UC patients with MH recruited, 45.4% reported functional bowel symptoms; functional constipation-like symptom (13.4%) was the most prevalent, followed by IBS-like symptom (10.9%), and functional diarrhea-like symptom (10.0%). The IBDQ-32 and SF-36 scores were significantly lower in MH patients with FBD-like symptoms than in those without FBD-like symptoms. Disease duration [odds ratio (OR): 1.022; p  < 0.001], body mass index (BMI; OR: 0.726; p  < 0.001) were independent predictors of FBD-like symptoms in UC patients with MH. Combining these two factors could attain area under the curve [0.786; 95% confidence interval (CI): 0.701–0.856, p  < 0.001] to predict FBD-like symptoms in MH patients. Conclusion: A number of UC patients with MH had accompanying FBD-like symptoms and significantly impaired QoL. Disease duration, BMI could predict the occurrence of FBD-like symptoms.